Assisted Reproduction Technology and Perinatal Outcomes: A Review - Ommolbanin Zare; Farin Soleimani (Mashhad University of Medical Sciences, 2017)
Introduction: Approximately 9% of couples worldwide face with infertility problem in some period of their life. Assisted reproductive technology (ART) is a common choice of treatment for many infertile couples that its case is male or female factor, or idiopathic. This review article was performed with aim to compare perinatal outcomes in different ART methods with each other and with spontaneous pregnancy. Methods: This review article was performed by searching in databases of PubMed, Medline, SID, Scopus, and The Cochrane Library from 2010 to 2016 to find the related articles with appropriate keywords such as Assisted reproductive techniques, Outcomes, Pregnancy). The English articles on the subject of assisted reproductive techniques and perinatal outcomes were included in the study and in the case of no access to the full text of the article and the unrelated results were excluded from the study. Results: According to the results of different studies, poor perinatal outcomes in ART pregnancies, including preterm birth, LBW, SGA and perinatal mortality were significantly higher in ART pregnancies compared with normal pregnancy. Conclusion: Multiple factors such as singleton or twin ART pregnancies, the type of used ART, treatment protocol, and the main cause of initial infertility affect perinatal outcomes.